2017
DOI: 10.1167/iovs.17-22065
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β1–43 Accumulates in the Lens Epithelium of Cortical Opacification in Japanese Patients

Abstract: PURPOSE.We investigated the accumulation of amyloid b (Ab 1-40 , Ab 1-42 , Ab ) in the lens epithelium of patients with opacification of five different types (cortical cataract [COR]; nuclear cataract [NUC]; posterior subcapsular cataract [PSC]; retrodots [RD]; and water clefts [WC]).METHODS. Samples were collected from Japanese patients taken during cataract surgery; Ab levels and mRNA expression were determined by ELISA and a real-time RT-PCR method, respectively.RESULTS. Levels of Ab 1-40 and Ab 1-42 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In addition, we show that the enhanced Aβ 1-43 ratio may be related to the onset and/or acceleration of diabetic cataracts. These findings support our previous studies [14][15][16], and may be useful in developing therapies for diabetic cataracts.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, we show that the enhanced Aβ 1-43 ratio may be related to the onset and/or acceleration of diabetic cataracts. These findings support our previous studies [14][15][16], and may be useful in developing therapies for diabetic cataracts.…”
Section: Discussionsupporting
confidence: 92%
“…The expressions of β-secretase and γ-secretase in mammalian lenses have been observed [11,12], and the accumulation of Aβ 1-40 and Aβ 1-42 has been reported in the cytosol of lens fiber cells from people with Alzheimer's disease [13]. We also reported that Aβ accumulates in the lens epithelium of humans with cortical opacification (senile cataracts) [14], and showed that the accumulation of Aβ in the lens accelerates lens opacification via nitric oxide-Aβ positive feedback [15]. Thus, these previous reports suggest that the accumulation of Aβ will be related to the onset of senile cataracts in studies using human lens samples.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations